2000
DOI: 10.1126/science.287.5455.1056
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Induced Apoptotic Neurodegeneration and Fetal Alcohol Syndrome

Abstract: The deleterious effects of ethanol on the developing human brain are poorly understood. Here it is reported that ethanol, acting by a dual mechanism [blockade of N-methyl-D-aspartate (NMDA) glutamate receptors and excessive activation of GABA(A) receptors], triggers widespread apoptotic neurodegeneration in the developing rat forebrain. Vulnerability coincides with the period of synaptogenesis, which in humans extends from the sixth month of gestation to several years after birth. During this period, transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

62
1,055
10
11

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,280 publications
(1,147 citation statements)
references
References 25 publications
62
1,055
10
11
Order By: Relevance
“…The immature brain is susceptible to widespread neuronal apoptosis secondary to a variety of insults including trauma, seizures, excessive oxygen, and certain drugs [36][37][38][39][40][41][42][43]. The observation that third-trimester gestational ethanol exposure can produce widespread neuronal apoptosis and neurobehavioral deficits led to the hypothesis that the adverse behavioral effects of AED exposure might bedue to asimilar mechanism [40,44].…”
Section: Aed-induced Neuronal Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…The immature brain is susceptible to widespread neuronal apoptosis secondary to a variety of insults including trauma, seizures, excessive oxygen, and certain drugs [36][37][38][39][40][41][42][43]. The observation that third-trimester gestational ethanol exposure can produce widespread neuronal apoptosis and neurobehavioral deficits led to the hypothesis that the adverse behavioral effects of AED exposure might bedue to asimilar mechanism [40,44].…”
Section: Aed-induced Neuronal Apoptosismentioning
confidence: 99%
“…The observation that third-trimester gestational ethanol exposure can produce widespread neuronal apoptosis and neurobehavioral deficits led to the hypothesis that the adverse behavioral effects of AED exposure might bedue to asimilar mechanism [40,44]. The effect of ethanol is mediated by combined NMDA glutamate receptor blockade and GABA A receptor activation [40,45], which are receptor mechanisms affected by some AEDs. Recently, several AEDs have been tested for similar effects in a neonatal rat model.…”
Section: Aed-induced Neuronal Apoptosismentioning
confidence: 99%
“…Ethanol triggers apoptotic neurodegeneration in the P7 rodent brain during the peak period of synaptogenesis that corresponds to the last trimester of pregnancy in humans [1,2]. The ethanolinduced neuronal loss may partially explain neuropathological conditions in rodents similar to those found in human fetal alcohol spectrum disorders (FASD).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, prenatal alcohol exposure in rodents has been shown to alter neurotransmitter functioning, including decreased DA uptake, deficits in serotonin reuptake sites, reduced density of NMDA receptor agonist binding sites, altered DA synthesis, and altered behavioral responses to dopaminergic drugs (Druse et al, 1990;Hannigan & Pilati, 1991;Kim & Druse, 1996;Maier, Chen, & West, 1996;Sutherland, McDonald, & Savage, 1997). Our own work has found that prenatal alcohol exposure contributed to altered DA neurotransmitter function in the striatum depending on the gestational timing of the alcohol exposure (Schneider et al, 2005).Because of the susceptibility of the developing brain to alcohol-induced apoptotic neurodegeneration (Ikonomidou et al, 2000), prenatal alcohol exposure could compromise cortical plasticity and therefore, acquisition of adaptive behavioral responses to environmental events. Both human and animal studies have concluded that prenatal alcohol exposure can disrupt myelination, as well as glial cells, which are critical for neuronal myelin development (Burden et al, 2005;Guerri, Pascual, & Renau-Piqueras, 2001;Sowell et al, 2001).…”
mentioning
confidence: 98%